An Empirical Model of Ionospheric Total Electron Content Based on Tide‐Like Signature Modeling - Haibing Ruan; Jiuhou Lei; Jianyong Lu; Fen Tang (Space Weather)
Abstract Accurate modeling of the total electron content (TEC) benefits scientific research and practical application. In this study, the global ionospheric maps from the Center for Orbit Determination of Europe (CODE) covering the years 2000–2021 are utilized to develop an empirical model of TEC by superposing the tide‐like components in the ionosphere. The tide‐like components, including the migrating and non‐migrating ones, are first derived from the daily CODE TEC data. Then, the sine and cosine components of a tide‐like signature are separately decomposed into the basic modes as a function of the modified inclination latitude with the principle component analysis, and the temporal evolution is regressed to the solar radiation dependence and interannual variation. As such, the climatological behavior of tidal amplitudes and phases could be well parameterized, and the developed model is capable of reproducing the global TEC patterns. The modeled TEC agrees well with the CODE input data with zero systematic error and a low root mean square error of 3.849 TECu, demonstrating a good model performance. This developed model, associated with the parametric tide‐like signatures, could serve as a background for future investigations of the ionospheric responses to the forcing from below or above.